Weight-adapted iodinated contrast media administration in abdomino-pelvic CT: Can image quality be maintained?. Issue 1 (February 2018) - Perrin, E.; Jackson, M.; Grant, R.; Lloyd, C.; Chinaka, F.; Goh, V.
Abstract: Introduction: In many centres, a fixed method of contrast-media administration is used for CT regardless of patient body habitus. The aim of this trial was to assess contrast enhancement of the aorta, portal vein, liver and spleen during abdomino-pelvic CT imaging using a weight-adapted contrast media protocol compared to the current fixed dose method. Methods: Thirty-nine oncology patients, who had previously undergone CT abdomino-pelvic imaging at the institution using a fixed contrast media dose, were prospectively imaged using a weight-adapted contrast media dose (1.4 ml/kg). The two sets of images were assessed for contrast enhancement levels (HU) at locations in the liver, aorta, portal vein and spleen during portal-venous enhancement phase. The t-test was used to compare the difference in results using a non-inferiority margin of 10 HU. Results: When the contrast dose was tailored to patient weight, contrast enhancement levels were shown to be non-inferior to the fixed dose method (liver p < 0.001; portal vein p = 0.003; aorta p = 0.001; spleen p = 0.001). As a group, patients received a total contrast dose reduction of 165 ml using the weight-adapted method compared to the fixed dose method, with a mean cost per patient of £6.81 and £7.19 respectively. Conclusion: Using a weight-adapted method of contrast media administration was shown to be non-inferior to a fixed dose method of contrast media administration. Patients weighing 76 kg, or less, received a lower contrast dose which may have associated cost savings. A weight-adapted contrast media protocol should be implemented for portal-venous phase abdomino-pelvic CT for oncology patients with adequate renal function (>70 ml/min/1.73 m 2 ). Highlights: Weight-adapted contrast regimes have the potential to reduce contrast dose in abdominopelvic CT. Patients weighing 76 kg or below received a lower contrast dose using a weight-adapted protocol. There are potential cost savings through implementing a weight-adapted protocol.